The First Evidence of Cryptosporidium meleagridis Infection in a Colon Adenocarcinoma From an Immunocompetent Patient - Kopacz, Żaneta; Kváč, Martin; Karpiński, Paweł; Hendrich, Andrzej B; Sąsiadek, Maria M; Leszczyński, Przemysław; Sak, Bohumil; McEvoy, John; Kicia, Marta (Frontiers in cellular and infection microbiology, 2019)
Objectives: The potential linkage between Cryptosporidium spp. infection and colorectal human cancer was suggested by limited reports showing higher prevalence of C. parvum and C. hominis in patients with colon cancer. Here we conducted research concerning presence of Cryptosporidium spp. in malignant tissue collected from patients with colorectal cancer. Methods: Cancerous colon tissue samples collected from 145 non-HIV infected patients with colorectal cancer were screened for Cryptosporidium spp. by immunofluorescence antibody test and genus-specific nested polymerase chain reaction followed by sequencing. Results: Screened pathogen was found in cancerous tissue originating from immunocompetent man with colon adenocarcinoma. Genotyping revealed presence of Cryptosporidium meleagridis. The presence of Cryptosporidium life cycle stages (oocysts and endogenous stages) in colon carcinoma tissue was confirmed by genus-specific FITC-labeling. Conclusions: Herein, we report on a C. meleagridis infection of a colon adenocarcinoma in an immunocompetent patient. This is the first report of C. meleagridis infection in the human colon and first evidence of active development of this species in cancer tissue.
Keywords: PCR; nádory tračníku; immunofluorescence labeling; adenokarcinom; Humans; Cryptosporidium meleagridis; genotyp; colon infection; kryptosporidióza; adenocarcinoma; colon cancer; Cryptosporidium; Adenocarcinoma; Cryptosporidiosis; Colonic Neoplasms; lidé; Genotype